Targeting kinesin family member 21B by miR-132-3p represses cell proliferation, migration and invasion in gastric cancer. Issue 4 (1st April 2022) - Liu, Bingtian; Qiang, Ling; Guan, Bingxin; Ji, Zhipeng
ABSTRACT: Recently, kinesin family member 21B (KIF21B) has been reported to be an oncogene in non-small cell lung cancer and hepatocellular carcinoma. However, the functional role of KIF21B and related molecular mechanisms in gastric cancer (GC) remain largely uncovered. In this study, online bioinformatics analysis showed that KIF21B was overexpression in GC and predicted poor prognosis. Consistently, we found that the protein expression of KIF21B was upregulated in GC tissues compared with adjacent tissues by immunohistochemistry. Knockdown of KIF21B significantly suppressed cell proliferation, migration and invasion in GC cell lines (AGS and SNU-5) using Cell counting kit‑8 (CCK-8) assay, colony formation and transwell assay. KIF21B was confirmed as the target of miR-132-3p in GC cells by luciferase reporter assay. Moreover, miR-132-3p was down-regulated and KIF21B expression was upregulated in GC tissues. Overexpression of KIF21B reversed the miR-132-3p-mediated suppressive effects on GC cell proliferation, migration and invasion. Furthermore, miR-132-3p overexpression downregulated the protein levels of Wnt1, c-Myc, β-catenin, proliferating cell nuclear antigen (PCNA) and N-cadherin, and upregulated E-cadherin expression in GC cells, which were all alleviated after KIF21B overexpression. In conclusion, our findings indicate that down-regulation of KIF21B by miR-132-3p suppresses cellular functions in GC, which might be linked to reduced Wnt/β-catenin signaling. Graphical abstract: uf0001